Christmas on my mind - Dailey, Janet (Kensington Publishing Corp., 2016)
Sheriff Ben Marsden of Branding Iron, Texas has no plans to attend the annual Christmas Ball until a pretty newcomer comes to town and gets involved in the planning. Jessica Ramsey's relatives seem to be in jail more than out, and Ben tells himself that's why he needs to keep an eye on her. As Jessica moves ahead to open a bed-and-breakfast with her mother, the future starts looking merry and bright.